A Low‐Intensity, High‐Frequency Intervention to Reduce Procrastination. Issue 4 (17th December 2020) - Wessel, Jason; Bradley, Graham L.; Hood, Michelle
Abstract : Studies assessing the efficacy of interventions aimed at reducing procrastination have generally lacked robust longitudinal measurement tools. Recent developments in communication technology and applications of the Experience Sampling Method (ESM) have made observations of such dynamic phenomena possible. We leveraged recent advancements in smartphone technology and ESM to measure delay associated with procrastination, while testing a low‐intensity, high‐frequency intervention to reducing that delay. First‐year university students ( N  = 107) reported their progress on an assignment twice daily over 14 days prior to the required submission date. Half ( n  = 51) were randomly allocated to an intervention condition in which they were also asked open‐ended questions designed to prompt reflection on four domains proposed to reduce procrastination, namely: expectancy, value, delay sensitivity, and metacognition . Multilevel mixed effect models revealed lower behavioral delay in the intervention condition compared to the control condition. This effect was strongest in those who at baseline scored below the median on trait procrastination. Behavioral delay over the 14‐day period was not associated with later assignment submission or lower assignment marks. These findings support a novel method for reducing delay and suggest procrastination can be alleviated in a wide range of contexts using relatively inexpensive and non‐intrusive strategies.